PENGARUH DAYA TARIK WISATA KULINER TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI RESTO APUNG, MUARA ANGKE, JAKARTA UTARA - Hani; Imam Ardiansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the influence of culinary tourism attractiveness on consumer purchase decisions at Resto Apung, Muara Angke, North Jakarta. Culinary tourism attractiveness in this study is measured through five dimensions, namely attraction, accessibility, amenities, ancillary, and activities. This study employed a quantitative approach with a causal associative research design. Primary data were collected by distributing questionnaires to 100 respondents who had visited Resto Apung and made at least one purchase. The sampling technique used was probability sampling, specifically simple random sampling. The data were processed using SPSS Statistics 25 and analysed using validity testing, reliability testing, classical assumption testing, multiple linear regression, t-tests, F-tests, and coefficient of determination. The results show that the dimensions of attraction, ancillary, and activities have a positive and significant effect on consumer purchase decisions. Meanwhile, the dimensions of accessibility and amenities do not have a significant partial effect on purchase decisions. Simultaneously, the five dimensions of culinary tourism attractiveness have a significant effect on consumer purchase decisions, with an F-count value of 35.222, which is greater than the F-table value of 2.47, and a significance value of 0.000. The Adjusted R Square value of 0.633 indicates that culinary tourism attractiveness explains 63.3% of consumer purchase decisions, while the remaining 36.7% is influenced by other factors beyond this study. The activities dimension is the most dominant factor influencing consumer purchase decisions at Resto Apung. Keywords: culinary tourism attractiveness, attraction, accessibility, amenities, ancillary, activities, purchase decision, Resto Apung